Testing the damping capacity of shape memory alloys - Foo, Raymond Mao Yann (2013)
In recent years, there has been an increasing interest in the study of shape memory alloys (SMAs) by many. This is because shape memory has two distinctive features and they are namely the shape memory effect and pseudoelasticity effect. The material also exhibits high damping capacity, biocompatibility and high kinetic output.